Temperature dependences of the effective diffusion coefficients for some ternary gas systems containing components of ammonia-synthesis - Zhavrin, Yu.I.; Kosov, V.N.; Poyarkov, I.V.; Asembaeva, M.K.; Fedorenko, O.V. (Recent Contributions to Physics, 2012)
The temperature dependences of the effective diffusion coefficients for two three-component gaseous systems consisting of the components that are used by the ammonia-synthesis in the temperature range 298 – 800 K are calculated. The obtained results should be used as a reference data.